Efficient transfer hydrogenation of alkyl levulinates to γ-valerolactone catalyzed by simple Zr–TiO2 metal oxide systems. (June 2022) - Zhao, D.; Su, T.; Rodríguez-Padrón, D.; Lü, H.; Len, C.; Luque, R.; Yang, Z.
Abstract: Zr–TiO2 synthesized heterogeneous catalysts could efficiently convert ethyl levulinates (ELs) to γ-valerolactone (GVL) using isopropanol (2-PrOH) as H-donor. Obtained catalysts were characterized by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), Scanning electron microscope (SEM), High revolution transmission electron microscope (HR-TEM), Fourier transform infrared spectroscopy (FT-IR), inductively coupled plasma optical emission spectroscopy (ICP-OES), NH3 /CO2 temperature programmed desorption (NH3 /CO2 -TPD), pyridine-infrared spectroscopy, H2 temperature-programmed reduction (H2 -TPR), and N2 adsorption and desorption measurements. In total, 10 wt% Zr–TiO2 with average nanoparticle sizes (ca. 4–6 nm) exhibited optimum catalytic activity after optimization of reaction temperature, reaction time, catalyst loading, as well as solvent effect. GVL yield reached 74% with 79% EL conversion at 190 °C for 5 h over 10 wt% Zr–TiO2 in 2-PrOH. The high catalytic activity could be attributed to an appropriate proportion of acidic/basic sites, high Brønted/Lewis acid ratio, and large surface areas. Both acidic and basic sites lead to a synergistic effect on the concurrent activation of H-donor and substrate. The major side product ethyl 4-hydroxypentanoate (EHP) and other byproducts were found. GVL yield achieved from methyl levulinate (ML) and levulinic acid (LA) were 65% and 20%, respectively. Catalyst deactivation was observed due to coke deposits on the catalyst's surface. The spent catalyst proved to be reusable to recover almost completely its initial activity after calcination (300 °C, 2 h). A plausible reaction mechanism is presented on the basis of characterization results. Highlights: Different materials based on varying Zr contents on TiO2 prepared via facile sol–gel hydrothermal method. Ten percent Zr–TiO2 exhibited efficient transfer hydrogenation toward EL to GVL. Spent catalyst regenerated to recover its initial activity after calcination (300 °C, 2 h).